The relationship between the church and state in community development: a case study of Caritas Zimbabwe - Madzirashe, Isdore (Midlands State University, 2017)
Developmental work is never a one man’s band but a call to both public and private players. While the government have the mandate by nature of its formation to engage in development work, the private sector comes in to augment the efforts of the government which are never enough especially when it comes to African governments who are ill funded. The world is so much impaired that it calls for many players to contribute for its’ positive and sensible development. Of ultimate importance in developmental work is positive peace build on a give and take relation. This study focuses on the relationship between the Church and State in development work, a case study of Caritas Zimbabwe Mutare Diocese. In the research it comes out clearly that the relationship between the Church and State in Zimbabwe has been a fluctuating one. The Church’s None Governmental Organizations have been taken to be agencies of regime change that is they are seen to be political in agenda and not really geared to be assisting the needy communities. As a measure to cube this fatal unexpected behavior the government has seen it necessary to call all NGOs including faith based NGOs to get registered; allocate them places to work and closely monitor them.